Executive functions in daily living skills: A study in adults with autism spectrum disorder - Yon-Hernández, Jo A.; Canal-Bedia, Ricardo; Wojcik, Dominika Z.; García-García, Laura; Fernández-Álvarez, Clara; Palacio-Duque, Stefanny; Franco-Martín, Manuel A. (Frontiers in Psychology, 2023)
Adults with autism and adults with schizophrenia show difficulties in adaptive skills, especially those related to daily functioning. Some studies suggest that adaptive skills are associated with deficits in executive functions (EF), while others indicate that intelligence quotient (IQ) might also play a role. Literature suggests that autistic symptoms further affect adaptive skills. The interest of the current study, therefore, was to explore to what extent IQ, EFs as well as core autistic symptoms predict adaptive skills. To do this, 25 controls, 24 adults with autism, and 12 with schizophrenia were assessed on IQ (Wechsler Adult Intelligence Scale), and executive functioning. The EF was measured with neuropsychological tasks (inhibition, updating, and task switching) and with the Dysexecutive-Spanish Questionnaire (DEX-Sp) which assessed everyday life EF problems. Core ASD symptoms were measured using the Autism Diagnostic Observation Schedule, the Autism Spectrum Quotient- Short version (AQ-S), and the Questionnaire for Repetitive Behavior in Adults- 2 (RBQ-2A). The results indicated EF difficulties in both, autism, and schizophrenia. The IQ explained a high percentage of the variance found in adaptive skills, but only in the autism group. We can conclude, therefore, that high IQ is associated with low adaptive skills levels and EFs affect adaptive functioning in people with autism; however, this does not explain the difficulties in adaptive functioning in the schizophrenia group. Core features of autism assessed with self-report questionnaires (but not the ADOS-2) predicted low scores on the adaptive skills, only in the autism group. Both EF measures predicted adaptive skills scores in autism, but not in schizophrenia. Our results suggest that different factors affect the adaptive functioning in each disorder. For instance, the EFs should be a central focus for improvement, especially for individuals with autism.